2016
DOI: 10.1021/acssuschemeng.5b01058
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Characterization of Biocompatible Oil-in-Water Nanoemulsion for Pesticide Delivery

Abstract: The formation of promising oil-in-water nanoemulsion suitable for pesticide delivery has been achieved by using methyl laurate as oil phase, and alkyl polyglycoside (APG) and polyoxyethylene 3-lauryl ether (C12E3) as mixed surfactant. Effects of APG and C12E3 mixing ratios, oil weight fraction, and total surfactant concentration on droplet size and distribution of the nanoemulsion were systematically investigated. Long-term stabilities of the nanoemulsions prepared with various surfactant mixing ratios were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 49 publications
1
89
0
Order By: Relevance
“…11. The linear variation of r 3 as a function of time indicated that Ostwald ripening was the driving force for instability, which was similar to the results obtained by Du et al 44 It was clearly illustrated that the slope increased with the increase in mR OS , which meant that the more stable nanoemulsions were formed with higher surfactant concentrations. These results were in agreement with previous research results.…”
Section: Stability Of the Bifenthrin Nanoemulsionsupporting
confidence: 86%
“…11. The linear variation of r 3 as a function of time indicated that Ostwald ripening was the driving force for instability, which was similar to the results obtained by Du et al 44 It was clearly illustrated that the slope increased with the increase in mR OS , which meant that the more stable nanoemulsions were formed with higher surfactant concentrations. These results were in agreement with previous research results.…”
Section: Stability Of the Bifenthrin Nanoemulsionsupporting
confidence: 86%
“…The similar herbicidal activities of NE and the commercial formulation, even with the lower NE deposition, could be attributed to potentiation of the biological activity when glyphosate was formulated as NE. In another paper, Du et al (2016) described the preparation and characterization of O/W NEs using laurate as oily phase and a mixture of two surfactants, alkyl polyglycoside (AL) and polyoxyethylene 3-lauryl ether (PLE). In order to evaluate the potential application of the NEs a model insoluble molecule, β-cypermethrin, was incorporated into the NEs.…”
Section: Nanoemulsions Applicable In Agriculturementioning
confidence: 99%
“…[30] Second, cosurfactant may diffuse from the interface film into the water phase upon dilution, leading the increase of free energy and decrease of interfacial film strength. [31] The droplet of the oil phase therefore get coalescence to reduce the free energy and interfacial area. Once the systems reach new balance again, the droplet size tend to stable with time.…”
Section: Dilution Stabilitymentioning
confidence: 99%